From Clay Tablets to Web: Journey of Library Catalogue - Kumar, Shiv (DESIDOC Journal of Library & Information Technology, 2013)
The paper discusses the evolution and development of library catalogues from clay tablets to theweb-based catalogue. In the early stages, cataloguing was a local and individual library practice. Eachlibrary constructed its own catalogue, most suited to its purpose. A series of continuous changes throughthe ages, in both, conventional and non-conventional catalogues, including recent technology inputsadded various features to the present day catalogue. Today the computerised catalogue may functionlike a portal and this function can be exploited infi nitely to connect to a variety of data considered usefulfor library users. The system designers are trying to adopt new trends in OPACs. Web-based cataloguesinitiated Web 2.0 trends like RSS feeds, blogs, downloadable e-media, and instant messages. The faceliftof the simple catalogue was eminent to keep up with the versatile needs of the widely web-exposedlibrary users. http://dx.doi.org/10.14429/djlit.33.1.3729